2014
DOI: 10.1016/j.cub.2014.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Induced Remodeling of the Bacterial Proteome

Abstract: Microorganisms live in fluctuating environments, requiring stress response pathways to resist environmental insults and stress. These pathways dynamically monitor cellular status, and mediate adaptive changes by remodeling the proteome, largely accomplished by remodeling transcriptional networks and protein degradation. The complementarity of fast, specific proteolytic degradation and slower, broad transcriptomic changes gives cells the mechanistic repertoire to dynamically adjust cellular processes and optimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
96
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(101 citation statements)
references
References 196 publications
(238 reference statements)
1
96
0
Order By: Relevance
“…Surprisingly, we found that the Pup ligase has a Pup-independent role in sporulation. P rotein homeostasis is a tightly regulated and critically important phenomenon in bacterial physiology (1). It is thought to be particularly complex in actinobacteria, which have both the canonical proteolytic machinery of prokaryotes and 20S proteasomes analogous to those of eukaryotes that are accompanied by a functional equivalent of ubiquitin known as the prokaryotic ubiquitin-like protein (Pup) (2)(3)(4)(5)(6)(7).…”
Section: Importancementioning
confidence: 99%
“…Surprisingly, we found that the Pup ligase has a Pup-independent role in sporulation. P rotein homeostasis is a tightly regulated and critically important phenomenon in bacterial physiology (1). It is thought to be particularly complex in actinobacteria, which have both the canonical proteolytic machinery of prokaryotes and 20S proteasomes analogous to those of eukaryotes that are accompanied by a functional equivalent of ubiquitin known as the prokaryotic ubiquitin-like protein (Pup) (2)(3)(4)(5)(6)(7).…”
Section: Importancementioning
confidence: 99%
“…The transcriptional and translational control of stress response is a well-known phenomenon and forms the basis of dramatic cellular reprogramming in response to environmental stress (reviewed in Chung, 2006;Guo and Gross, 2014;Shimizu, 2013). An elaborate interconnected network of pathways is involved in regulating translation in response to varied stresses such as nutrient deprivation, pH, ionic strength, and temperature (Wilson and Nierhaus, 2007).…”
Section: Figmentioning
confidence: 99%
“…While it is recognized that certain common phenomena underlie generalized stress responses (Guo and Gross, 2014), studies aimed at identifying central stress response proteins could only conclude that every stress response has a specialized mechanism of action. Cross-stress protection, the ability of one stress condition to provide protection against other stressors, also suggests a central control of stress response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is in this compartment where most of the perception of the bacterial surroundings takes place. Sensory devices, usually periplasmic-protruding inner-membrane histidine kinases or antisigma factors, detect changes in the environment and transduce this information to cytoplasmic effectors, usually transcriptional regulators (2,3). This simple array provides an efficient and rapid response to modulate the expression of factors required to cope with a continuously challenging environment.…”
mentioning
confidence: 99%